Optimizing Diagnosis and Antibiotic Therapy in Ventilator-Associated Pneumonia: A Comparative Study of Tracheal Secretion Cultures in Critically III Patients - Muhammad Rizky Assilmy Lubis; Syamsul Bihar (Jurnal Impresi Indonesia, 2025)
Invasive mechanical ventilation in pneumonia patients often leads to complications, including ventilator-associated pneumonia (VAP), which is associated with specific bacterial pathogens and antibiotic resistance. Tracheal secretion cultures are essential for identifying bacterial patterns and assessing antibiotic resistance in these patients. This study aims to analyze the bacterial patterns and antibiotic resistance in tracheal secretion cultures of pneumonia patients undergoing invasive mechanical ventilation in a hospital setting. This cross-sectional study involved 95 samples from patients receiving care in the intensive care unit (ICU) who met predefined inclusion and exclusion criteria. Samples were collected through endotracheal aspiration or bronchoalveolar lavage procedures. Bacterial identification was conducted using both conventional and automated methods, while antibiotic resistance was assessed using the disk diffusion method. The study found that Gram-negative bacteria, primarily Acinetobacter baumannii and Pseudomonas aeruginosa, dominated the bacterial cultures. These pathogens are known for their high adaptability in hospital environments and their association with prolonged hospitalization and increased mortality. High resistance to ?-lactam antibiotics and fluoroquinolones was observed, although antibiotics like amikacin and meropenem remained effective. Chi-square analysis showed a significant correlation between bacterial species and antibiotic resistance patterns. The findings highlight the importance of accurate microbiological diagnosis to guide appropriate empirical therapy and emphasize the need for strict antibiotic stewardship programs and continuous resistance surveillance in ICU settings. Further studies are necessary to optimize infection control and antibiotic therapy protocols for patients requiring prolonged mechanical ventilation.